Water Variables Analysis Using a Concept of Principal Component Statistics in Etim Ekpo River, Niger Delta Zone, Nigeria - Akpan, I. I.; Jonah, U. E.; Ite, A. E.; Ukekpe, U. S.; Raphael, M. P. (European Journal of Applied Sciences, 2023)
Water Variables Analysis through a concept of principal component statistics (PCS) was studied in Etim Ekpo River, Niger Delta Zone, Nigeria from January, 2020 -December, 2021 at three designated stations. Seventeen water variables were studied and analysed using various prescribed standards. A total of 34 samples were collected at all stations. The principal component statistics (PCS) was employed in the analysis of the water variables. The principal components adopted were that which contained the highest percentage of the total variance of information in the original data set. The results showed that the loading factors were basically, temperature, dissolved oxygen (DO), sodium (Na), Electrical Conductivity (Ec), total suspended solids (TSS), Acidity (A), Magnesium (Mg), Total Hardness (TA), Total Dissolved Solids (TDS) Sulphate (So4), Phosphate (Po4-P), Total Alkalinity (TA). These could be aligned as: nutrient loading factors, organic loading factors, domestic loading factors and chemo-physical loading factors. In a nutshell, the water variable analysis tickle within the prescribed standards of various organizations, which is perfect to sustain the aquatic biota. However, the quest of anthropogenic advancement should be checked, which might increase loading factors in the system.